Elevated CNS Inflammation in Patients with Preclinical Alzheimer's Disease. Issue 1 (January 2014) - Monson, Nancy L; Ireland, Sara J; Ligocki, Ann J; Chen, Ding; Rounds, William H; Li, Min; Huebinger, Ryan M; Munro Cullum, C; Greenberg, Benjamin M; Stowe, Ann M; Zhang, Rong
Alzheimer's disease (AD) is a progressive, neurodegenerative disease that may involve inflammatory responses in the central nervous system (CNS). Our objective was to determine whether patients with amnestic mild cognitive impairment (aMCI), a preclinical stage of AD, have inflammatory characteristics similar to patients with multiple sclerosis (MS), a known CNS inflammatory disease. The frequency of lymphocytes and levels of pro-inflammatory cytokines in the cerebrospinal fluid of aMCI patients was comparable to MS patients or patients at high risk to develop MS. Thus, brain inflammation occurs early at the preclinical stage of AD and may have an important role in pathology.